牙周基础治疗对伴2型糖尿病的中、重度牙周炎患者牙周炎症控制、血清炎症指标及代谢水平影响 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2014)
OBJECTIVE: To evaluate the effects of periodontal treatment on the clinical response, systemic inflammatory parameters, and metabolic control of type 2 diabetes patients with moderate to severe periodontitis. METHODS: A total of 56 patients with mean clinical attachment level (CAL)>3 mm were included in the subgroup analysis. A repeated-measures ANOVA (group factor: treatment group and control group; time factor: initial visit, 1.5, 3, and 6 months) was used to analyze the probing depth (PD), CAL, bleeding on probing (BOP), high-sensitivity C-reactive protein (hsCRP), glycated hemoglobin (HbA1c), and fasting plasma glucose. RESULTS: Significantly lower PD (F=62.898，P=0.000), CAL (F=51.263，P=0.000), BOP (F=75.164，P=0.000), hsCRP (F=6.391, P=0.010), HbA1c (F=4.536, P=0.011), and fasting plasma glucose level (F=3.073，P=0.031) were observed after therapeutic periodontal improvement. The inter-group differences for PD (t=−2.050，P=0.045), BOP (t=−4.538，P=0.000), and hsCRP (t=−2.261, P=0.028) were statistically significant after therapy. CONCLUSION: Non-surgical periodontal treatment can effectively improve periodontal status, circulating inflammatory status, and metabolic control of diabetic patients with moderate to severe periodontitis.